3D Tracking and Nuke Compositing. - Morse, Brian (linkedin.com, 2017)
Discover how to use 3D tracking data to add 3D objects to a 2D shot in Nuke. Speed up your workflow by learning to set up your 3D scene once and use it for all of your shots.